Reeder and Felson’s Gamuts in Radiology Comprehensive Lists of Roentgen Differential Diagnosis - Reeder, Maurice M. (Springer New York, 2003)
Gamuts in Radiology is the world's most complete, best known, and most trusted guide to radiologic differential diagnosis. Since 1975, radiologists the world over have used 'Gamuts' to ensure that every diagnostic possibility is considered. For the Fourth Edition, Dr. Maurice M. Reeder has assembled an all-new board of Section Editors who have completely revised and updated their respective sections. These editors are among the world's authorities in their respective specialties, and they have given this classic the most complete revamping it has ever had. New features in the fourth edition include: over 250 new gamuts in the areas of ultrasound, magnetic resonance body imaging, and head and neck imaging; more than 80 percent of the previously existing gamuts have been updated; an entire new section on Obestetrical Ultrasound
Keywords: Imaging / Radiology; Radiology, Medical; Röntgendiagnostik; Medizinische Radiologie; Differentialdiagnose; Skala